Chemical composition and bio-functional perspectives of Erica arborea L. extracts obtained by different extraction techniques: Innovative insights - DOĞAN, AHMET; EMRE, GİZEM; ŞENKARDEŞ, İSMAİL (ELSEVIER, 2019)
Erica arborea L., also known as Estrella Gold, is traditionally used for several purposes. In this research, five different extraction techniques: accelerated solvent extraction (ASE), microwave-assisted extraction (MAE), maceration (MAC), soxhlet (SOE) and ultrasound-assisted extraction (UAE) were used to compare the total phenolic, flavonoids, total antioxidant activity and enzymatic activities of E. arborea extracts obtained different extraction techniques. The total phenolic and flavonoid contents were in the order of ASE > MAE > SOE > MAC > UAE. All extracts showed antioxidant, anticholinesterase, anti-tyrosinase and anti-diabetic activities. A highly sensitive method using ultra-high-pressure liquid chromatography coupled with linear ion trap-Orbitrap tandem mass spectrometry (UHPLC-LTQ-Orbitrap-MS) has been used for the qualitative analysis of obtained extracts. Seventy-two polyphenolic compounds were identified in all extracts. However, 20 components were quantified among the extracts. ASE was found to be a better extraction technique as compared to the other extraction techniques. E. arborea can be exploited in the discovery of bioactive natural products for the treatment of Alzheimer's disease, diabetes and pigmentation problems.
Keywords: Green extraction; Phenolics; Antioxidant; Enzyme inhibition; Multivariate analysis; ANTIOXIDANT PROPERTIES; PHENOLIC-COMPOUNDS; ASSISTED EXTRACTION; PROFILE; OPTIMIZATION; FLAVONOIDS; PLANTS; PROANTHOCYANIDINS; GLYCOSIDES; CAPACITY